Hadith #189 - Sahih al-Bukhari - Abu Shihab (Sahih al-Bukhari)
Mahmud bin Ar-Rabi` who was the person on whose face the Prophet (ﷺ) had ejected a mouthful of water from his family’s well while he was a boy, and `Urwa (on the authority of Al-Miswar and others) who testified each other, said, “Whenever the Prophet (ﷺ) , performed ablution, his companions were nearly fighting for the remains of the water.”
Grade: Sahih

Hadith #512 - Sahih al-Bukhari - Abu Shihab (Sahih al-Bukhari)
Once `Umar bin `Abdul `Aziz delayed the prayer and `Urwa bin Az-Zubair went to him and said, “Once in ‘Iraq, Al-Mughira bin Shu`ba delayed his prayers and Abi Mas`ud Al-Ansari went to him and said, ‘O Mughira! What is this? Don’t you know that once Gabriel came and offered the prayer (Fajr prayer) and Allah’s Messenger (ﷺ) prayed too, then he prayed again (Zuhr prayer) and so did Allah’s Apostle and again he prayed (`Asr prayers and Allah’s Messenger (ﷺ) did the same; again he
Grade: Sahih

Hadith #1514 - Sahih al-Bukhari - Abu Shihab (Sahih al-Bukhari)
I left for Mecca for Hajj-at-Tamattu` assuming Ihram for `Umra. I reached Mecca three days before the day of Tarwiya (8th Dhul-Hijja). Some people of Mecca said to me, “Your Hajj will be like the Hajj performed by the people of Mecca (i.e. you will lose the superiority of assuming Ihram from the Miqat). So I went to `Ata’ asking him his view about it. He said, “Jabir bin `Abdullah narrated to me, ‘I performed Hajj with Allah’s Messenger (ﷺ) on the day when he drove camels with him. T
Grade: Sahih